Original CIN: reviewing roles for APC in chromosome instability - Rusan, Nasser M. (The Rockefeller University Press, 2008)
You may have seen the bumper sticker “Eve was framed.” Thousands of years of being blamed for original sin and still many wonder, where's the evidence? Today, the tumor suppressor adenomatous polyposis coli (APC) may have the same complaint about accusations of a different type of CIN, chromosome instability. A series of recent papers, including three in this journal, propose that loss of APC function plays an important role in the CIN seen in many colon cancer cells. However, a closer look reveals a complex story that raises more questions than answers.